Gambaran Tingkat Stress dan Stressor Guru Sekolah Dasar di Pedesaan dengan Sistem Pembelajaran Tatap Muka Terbatas pada Era Pandemi Covid-19 - Lisna Sari; Veny Elita; Darwin Karim (HEALTH CARE : JURNAL KESEHATAN, 2022)
Introduction: the pandemic has caused a lot of stress for teachers. Especially with changing systems in teaching, including teachers in rural areas. Stress on teachers is caused by many things such as the individual, families, communities and the environment. This study aimed to describe the stress level and stressor of elementary school teachers in rural areas with a limited classroom learning in the era of the covid 19 pandemic. Methods: This study used a quantitative research design using a descriptive method. The sample included 68 teachers from 21 elementery schools in Siak Kecil District, Bengkalis Regency, Riau Province, Indonesia who were taken based on inclusion criteria using cluster random sampling technique. Results: the results showed that the majority of respondents were late adulthood (39.7%) and the majority of the respondents' gender was female (73.5%), education of respondents was bachelor degree (97.1%), marital status of married respondents (94.1%). On the subjects taught The majority are classroom teachers (67.6%), most teachers only teach in the same class (77.9%). From 68 Respondents, 45 teachers (66.2%) experienced severe stress and the majority of stressors related to the individual (57.4%). Conclusion: the stress level of elementery teachers in rural areas with a limited classroom learning in the era of the covid 19 pandemic was at a severe level with the majority of stressors are coming from individuals.